An Analysis of Ferienjob Practices in Germany: Modus Operandi, Legal Actions, Prevention, and Global Comparisons - Bayuna, Kadek Ari; Shinto Bina Gunawan Silitonga; Bhaskara Ardhy Anugerah Nasution (Jurnal Ilmu Kepolisian, 2024)
The Ferienjob program in Germany which was started as an opportunity for students to find work and earn an income during vacations has of late come under criticism and allegations of being justifications for more nefarious endeavors such as human trafficking and labor slavery. In the light of this background, this article examines the factors that facilitated the exploitation of over 1,000 Indonesian and Uzbek students engaged in the Ferienjob scheme arguing about weaknesses in the host and the students’ home countries’ labor protection systems. Even though there are labor laws in Germany like the Employengesetz which forbids the exploitation of minor employees and the Mindestlohngesetz which ensures at least a guaranteed pay for every employee’s work, exploited labor has not died down and students remain to be in low wage and unsafe working conditions due to the contracts that they deal with. The research includes questions regarding the qualitative methodology that reflects both primary data collected through the interviews and secondary data obtained from government documents and legislations. The key study findings include the use of false claims in this particular case to lure in students, the stealing of the student’s money via placement fees, and the lack of proper legal care for foreign employees. The article further examines the responses issued by Indonesia and Germany in the court trying to show that it is extremely hard to bring the offending parties to book and to coordinate the protection of labor laws. As a final point the study provides the suggestions of how the preventive measures could be improved including enhanced regulations for recruitment firms, an improvement in the control of international agencies, and improvement of university partnerships.